Best practices in innovation: a survey in companies of the IT sector - Castanheira de Souza, Júlio Cesar; Pereira Barbosa, José Geraldo; Carino Bouzada, Marco Aurélio; Gonçalves, Antônio Augusto; Tavares, Elaine (Revista de Administração da UFSM, 2015)
This research aimed to assess the extend to which the adoption, to a greater or lesser degree, of management practices recommended by the innovation management model suggested by Tidd and Hull (2003) explain, together with the context, the seventh model component, the performance of both service innovation and in service delivery process, of 36 information technology companies established in the Rio de Janeiro state. The research identified that the component of the model that discriminated the highest number of performance indicators of service innovation was the context (environment) in which the companies operate. The result of logistic regression performed indicated that the reciprocal integration ability and the existence of a product development sector in the company organizational structure, the internal dimension of context, were the two elements determinant to a company be above or below average in terms of performance in developing service innovations. Finally, the results indicated, with a moderate correlation with a significance level of 0.01, a good performance in service innovation implies in a good performance in delivering the new or improved services.